Influencia de la labranza cero o siembra directa sobre las propiedades físicas del suelo agrícola de la provincia de Los Ríos, Ecuador - Suarez Insuasti, Pascual Benito (2019)
The quality of the physical properties of the soils, are commonwith communicated with the tillage of conservation, this comes to reduce the carbon dioxide emissions that cause the greenhouse effect. In this sustainable system it allows to establish critical levels indicators of physical quality by assigning large factors that increase the weight of productivity in crops. However, the main problem today is the decrease in the application of this method, which apart from reducing production costs quantifies farmers' economic incomes. By way of discussion, it is established that zero tillage or direct planting constitutes a positive effect on the physical properties of agricultural soils, in particular on the increase in apparent density, porosity and hydraulic conductivity. The province of Los Ríos located in the center of Ecuador, produces large tracts of crops of great importance to the economy of the country; and a compilation that differentiates the values of these factors in the application of conventional planting and direct planting is essential information for the farmer. From a technical point of view, the research establishes an existing influence on direct planting on the physical properties of agricultural soils in the northern, central and southern region of the province of Los Ríos. In the Apparent Density (DA) factor in the three regions where studies have been conducted on direct planting shows high ranges (1.17 to 1.35 mg/cm3) compared to conventional planting. In terms of porosity factors (47.49 -58.50 % v/v), Moisture retention (19.12 – 44.67%), and Organic matter (4.0 – 6.0 %) expose dominance in terms of direct planting or zero tillage